Management of dysphagia and gastroparesis in Parkinson’s disease in real-world clinical practice – Balancing pharmacological and non-pharmacological approaches - Bhidayasiri, Roongroj; Phuenpathom, Warongporn; Tan, Ai Huey; Leta, Valentina; Phumphid, Saisamorn; Chaudhuri, K. Ray; Pal, Pramod Kumar (Frontiers in Aging Neuroscience, 2022)
Gastrointestinal (GI) issues are commonly experienced by patients with Parkinson’s disease (PD). Those that affect the lower GI tract, such as constipation, are the most frequently reported GI problems among patients with PD. Upper GI issues, such as swallowing dysfunction (dysphagia) and delayed gastric emptying (gastroparesis), are also common in PD but are less well recognized by both patients and clinicians and, therefore, often overlooked. These GI issues may also be perceived by the healthcare team as less of a priority than management of PD motor symptoms. However, if left untreated, both dysphagia and gastroparesis can have a significant impact on the quality of life of patients with PD and on the effectiveness on oral PD medications, with negative consequences for motor control. Holistic management of PD should therefore include timely and effective management of upper GI issues by utilizing both non-pharmacological and pharmacological approaches. This dual approach is key as many pharmacological strategies have limited efficacy in this setting, so non-pharmacological approaches are often the best option. Although a multidisciplinary approach to the management of GI issues in PD is ideal, resource constraints may mean this is not always feasible. In ‘real-world’ practice, neurologists and PD care teams often need to make initial assessments and treatment or referral recommendations for their patients with PD who are experiencing these problems. To provide guidance in these cases, this article reviews the published evidence for diagnostic and therapeutic management of dysphagia and gastroparesis, including recommendations for timely and appropriate referral to GI specialists when needed and guidance on the development of an effective management plan.